Chickadee ebook - Erdrich, Louise (The Birchbark House, 2012)
Winner of the Scott O'Dell Award for Historical Fiction, Chickadee is the first novel of a new arc in the critically acclaimed Birchbark House series by New York Times bestselling author Louise Erdrich. Twin brothers Chickadee and Makoons have done everything together since they were born—until the unthinkable happens and the brothers are separated. Desperate to reunite, both Chickadee and his family must travel across new territories, forge unlikely friendships, and experience both unexpected moments of unbearable heartache as well as pure happiness. And through it all, Chickadee has the strength of his namesake, the chickadee, to carry him on. Chickadee continues the story of one Ojibwe family's journey through one hundred years in America. School Library Journal, in a starred review, proclaimed, "Readers will be more than happy to welcome little Chickadee into their hearts."